Blasphemy as a Criminal Offence: Legal Transformation in Indonesia from Colonial Era to Modern - Rokhmad, Abu; Saifudin, Saifudin; Sunandar, Sunandar; Nurdin, Nazar (Walisongo Law Review (Walrev), 2024)
This paper was written to answer three important questions, namely knowing the narrative trend and the transformation model for blasphemy offenses in Indonesian legislation. Religious offenses are the only state instrument to crackdown on perpetrators of blasphemy. The implementation of the blasphemy offense in practice has been criticized, especially in relation to human rights violations. The results of this study confirm three things, firstly, religious offenses were first regulated through a Circular Letter of the Supreme Court in 1964 and PNPS Number 1 1965 which were designed to prevent the deviation of religious teachings and to protect religious peace. Blasphemy offenses were included in the Criminal Code in the New Order, then strengthened in the Reformation Era by incorporating blasphemy offenses into Law No. 11 of 2008. Second, the transformation of religious offenses stems from the British code applied in India, adopted by the Dutch colonial government and used in the region. Dutch East Indies because there are many similarities in cultural diversity between India and Indonesia. Third, the conception of religious offenses in KUHP makes religious blasphemy the basis for criminal acts. Religion is not the only element of a crime, but as an element that is an important part of a crime. Implementation of the guarantee of freedom of religion is indeed not easy to do because of differences in the definition of religion and freedom of religion; different definitions of human rights; and differences in the meaning of human rights protection. Tulisan ini ditulis untuk menjawab tiga pertanyaan penting, yakni mengetahui tren narasi dan model transformasi tindak pidana penodaan agama dalam peraturan perundang-undangan di Indonesia. Delik agama merupakan satu-satunya instrumen negara untuk menindak pelaku penodaan agama. Penerapan tindak pidana penodaan agama dalam praktiknya banyak menuai kritik, terutama terkait dengan pelanggaran hak asasi manusia. Hasil penelitian ini menegaskan tiga hal, pertama, delik keagamaan pertama kali diatur melalui Surat Edaran Mahkamah Agung tahun 1964 dan PNPS Nomor 1 Tahun 1965 yang dirancang untuk mencegah penyimpangan ajaran agama dan menjaga ketentraman umat beragama. Delik penodaan agama dimasukkan dalam KUHP pada masa Orde Baru, kemudian diperkuat pada Era Reformasi dengan memasukkan delik penodaan agama ke dalam Undang-Undang Nomor 11 Tahun 2008. Kedua, transformasi delik keagamaan bermula dari KUHP Inggris yang diterapkan di India, yang diadopsi oleh KUHP. Pemerintah kolonial Belanda dan digunakan di wilayah tersebut. Hindia Belanda karena banyak kesamaan keanekaragaman budaya antara India dan Indonesia. Ketiga, konsepsi delik agama dalam KUHP menjadikan penodaan agama sebagai dasar tindak pidana. Agama bukan satu-satunya unsur suatu kejahatan, namun sebagai unsur yang menjadi bagian penting dalam suatu kejahatan. Implementasi jaminan kebebasan beragama memang tidak mudah dilakukan karena adanya perbedaan definisi agama dan kebebasan beragama; definisi hak asasi manusia yang berbeda; dan perbedaan makna perlindungan hak asasi manusia